A Rare Case of Hutchınson-Gılford Progerıa Syndrome wıth Early Dental Loss wıthout Decay - Pekdemir, Tuğçe N; Öztürk, Duygu; Çetindağ, Merve T; Akleyn, Ebru; Sarıyıldız, Cansu O; Callea, Michele; Yavuz, İzzet (Makara Journal of Health Research, 2018)
Hutchinson-Gilford progeria syndrome (HGPS) is a rare autosomal recessive genetic disorder that occurs as a point mutation in the LMNA gene. It is a rare hereditary disorder, with approximately 100 cases reported in the medical literature. These patients and our case show features of aged appearance (pseudosenilism), loss of subcutaneous fat texture, growth retardation, sclerodermatous skin, ‘horse riding posture', bird-face appearance, beaked nose, high pitched voice, protruding knees and elbows, underweight, short stature, malformation of the teeth, micrognathia, hypodontia, malocclusion, craniofacial disproportion, atherosclerosis and cardiovascular disorders. Unlike typical findings of HGPS, diffuse alopecia and prominent scalp veins were not observed in our case. Patients with HGPS have an average life span of 13 years, owing to myocardial infarction and congestive heart failure and our case also has atherosclerosis and heart failure. Here, we report extra- and intraoral findings in a 24-year-old male patient with HGPS who came to our faculty with complaints about absence of teeth and psychological problems caused by absence of teeth and HGPS findings such as pseudosenilism, growth retardation and short stature. We have described necessary dental examinations and treatments for our patient and have reviewed the literature.